The Effect of E-Warong Accessibility on Household Consumption - Oktavia, Sari; Djamaluddin, Sartika (Pelopor Publikasi Akademika, 2024)
BPNT/Sembako is a social assistance program provided by the government to improve the welfare of people experiencing poverty by providing food with balanced nutrition and providing choice and control over food. BPNT/Sembako uses e-wrong as the only distribution. Households must come to e-wrong with a KKS. Because e-wrong is the only place for distribution, e-wrong is very important, including the distance of the e-wrong from the location of the beneficiary. However, e-wrong still has a limited distribution. The purpose of this study is to generally investigate the effectiveness of the e-wrong program and specifically investigate the effect of e-wrong accessibility on household consumption, especially rice consumption, taking into account aspects of price and quality of rice, characteristics of other consumer goods, household characteristics, residential area characteristics, local government assistance, and consumption motivation. This study uses 4-month panel data (November 2019-February 2020) of BPNT/Sembako recipients in the March 2020 Susenas and the random effects (RE) approach. The results of the study show that the accessibility of e-warong has a significant effect on household consumption (rice consumption). The farther the e-warong is, the higher the consumption of rice.